Cardiotoxicity associated with immune checkpoint inhibitors: Current status and future challenges - Gan, Lu; Liu, Demin; Ma, Yanan; Chen, Xuening; Dai, Aihui; Zhao, Sihan; Jin, Xiaoxue; Gu, Guoqiang (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors (ICIs) are the most notable breakthrough in tumor treatment. ICIs has been widely used in tumor patients, but its wide range of immune-related adverse events (irAEs) should not be ignored. irAEs can be involved in any organ system, including immune-related cardiotoxicity. Although the cardiotoxicity induced by immune checkpoint inhibitors is rare, it is extremely lethal and has attracted increasing attention. PD-1 and PD-L1 are expressed in human cardiomyocytes, so the application of PD-1/PDL-1 inhibitors can cause many adverse reactions to the cardiovascular system. This review summarizes the latest epidemiological evidence on the cardiovascular toxicity of programmed cell death protein-1(PD-1)/programmed cell death ligand-1(PD-L1) inhibitors and the clinical manifestations, as well as the potential pathological mechanisms. These updates may provide a novel perspective for monitoring early toxicity and establishing appropriate treatment for patients with ICI-related cardiotoxicity.